Organized Out‐of‐School Activities and Peer Relationships: Theoretical Perspectives and Previous Research1. Issue 140 (13th June 2013) - Fredricks, Jennifer A.; Simpkins, Sandra D.
Abstract: The goal of this volume is to show how organized activities provide an ideal setting for developing a deeper understanding of peer relations, as well as offering a context for a more positive study of peers. The chapters in this volume focus on youth 10 to 18 years of age. In this introductory chapter we first describe the reasons why organized activities, like sports, arts, and school clubs, are ideal settings to examine peer processes. Next, we describe the theoretical and empirical research related to two questions: (1) how do peers influence organized activity participation and (2) how does organized activity participation influence peer relations. We organize this review around three themes outlined in the broader peer relations literature: (1) peer groups, (2) peer relationships, and (3) peer interactions. © 2013 Wiley Periodicals, Inc.